Sand Live Oak, Quercus geminata - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Sand live oak is found throughout northern Florida, more broadly west to Louisiana, and northeast to North Carolina. It is found in beach dunes, backdunes, sandhills, coastal areas, and inland areas with deep sandy soils. While this plant forms trees farther inland, it is commonly reduced to shrubs and sub-shrubs because of the extreme environmental conditions of the coast. The acorns of this plant are a valuable food source for wildlife. Sand live oak is available also in commercial nurseries and is often used as a landscape plant. https://edis.ifas.ufl.edu/sg182